Detection of novel gammaherpesviruses from fruit bats in Indonesia. Issue 3 (March 2018) - Wada, Yuji; Sasaki, Michihito; Setiyono, Agus; Handharyani, Ekowati; Rahmadani, Ibenu; Taha, Siswatiana; Adiani, Sri; Latief, Munira; Kholilullah, Zainal Abidin; Subangkit, Mawar; Kobayashi, Shintaro; Nakamura, Ichiro; et al.
Abstract : N/A: Bats are an important natural reservoir of zoonotic viral pathogens. We previously isolated an alphaherpesvirus in fruit bats in Indonesia, and here establish the presence of viruses belonging to other taxa of the family Herpesviridae. We screened the same fruit bat population with pan‐herpesvirus PCR and discovered 68 sequences of novel gammaherpesvirus, designated 'megabat gammaherpesvirus' (MgGHV). A phylogenetic analysis of approximately 3.4 kbp of continuous MgGHV sequences encompassing the glycoprotein B gene and DNA polymerase gene revealed that the MgGHV sequences are distinct from those of other reported gammaherpesviruses. Further analysis suggested the existence of co‐infections of herpesviruses in Indonesian fruit bats. Our findings extend our understanding of the infectious cycles of herpesviruses in bats in Indonesia and the phylogenetic diversity of the gammaherpesviruses.